Active aging: a right or a duty? - Mendes, Felismina (2013)
It was in the developed countries that the increase in the aging of the population began, though it has evolved most markedly in the developing countries in recent years. It is estimated that global aging in the 21st century will result in a substantial increase in demand for social, economic and health solutions all over the world, at unsustainable costs for future generations. Active aging emerges today as a concept that, according to the World Health Organisation, reflects the importance of psychological, psychosocial and social factors when devising intervention to foster adaptation to aging. WHO considers the word active to mean ongoing participation in social, economic, cultural, spiritual and civic issues and not just a person's ability to be physically active or continue to work. Social, demographic, financial and political incentives to bear the costs of longevity have sanctioned and consolidated the paradigm of active aging, which, anchored in its social utility, has gradually become compulsory. The discussion of the assumptions underlying this paradigm brings us to this analysis, which conducts critical reflection on the current concept of active aging and the way in which this concept is understood and implemented in the political, economic and social sphere. The conclusion is that the ideology of people's obligation and implicit responsibility makes active aging compulsory and an exclusionary practice to which only a few have access. We also find that critical sociological analysis has failed to address this issue.